Aplikasi Trichoderma sp. dan pupuk NPK terhadap pertumbuhan dan hasil tanaman kedelai (Glycine max L.) varietas Grobogan - Denny Sudrajat; Zainal Mutaqin; Evi Yunita Sari; Juwita Suri Maharani; Yuriansyah Yuriansyah (Politeknik Negeri Lampung, 2023)
Soybean imports in Indonesia show that national soybean production is still low and efforts are needed to increase production. One way to increase edamame production is the application of Trichoderma sp. and NPK fertilizers. The purpose of this study is to determine the effect of the application dose of Trichoderma sp. and NPK fertilizers and their combinations on the growth and yield of soybean plants. This study used a factorial Randomized Block Design (RBD) consisting of two factors, namely Trichoderma sp and doses of NPK fertilizer, repeated 3 times so that there were 30 experimental units. The treatment consisted of: factors (a) Trichoderma sp. dose: a0= 0 g/plant; a1= 5 g/plant; a2= 10 g/plant; a3= 15 g/plant; and a4 = 20 g/plant. Factor (b) NPK fertilizer dosage from 2 levels, namely: b1 = 250 kg/ha and b2 = 300 kg/ha. The results of this study are: (1) administration of Trichoderma sp. independently affects the growth observation variable in the vegetative phase of the plant, but does not significantly affect production; (2) NPK fertilizer independently affects plant growth in the vegetative phase and production yields; (3) combination treatment of Trichoderma sp. 15 g/plant and 250 kg/ha of NPK fertilizer gave the highest seed weight per plant, namely 30.95 g; and (4) there is an interaction effect between the Trichoderma sp. treatments. and NPK fertilizer on seed weight per plant.